Effectiveness of a simplified method for isolation of Burkholderia pseudomallei from soil. - Limmathurotsakul, D; Wuthiekanun, V; Amornchai, P; Wongsuwan, G; Day, N; Peacock, S (2012)
Detection of environmental Burkholderia pseudomallei indicates a risk for melioidosis and is important for the development of a global risk map. We describe a simple method for detecting B. pseudomallei using direct culture of soil in enrichment broth. This gives a rate of positivity comparable to that obtained with a standard method but is cheaper and labor saving.